From Der Cid / The Cid - Johann Gottfried Herder (Song Loves the Masses, 2017)
Don Diego sat in deep sadness, Never had one been so mournful; Full of grief, he pondered day and night The disgrace that had befallen his house. The disgrace of the ancient, noble Heroism of the house of Lainez , Which had exceeded that of the ...